The mysterious mr quin - Christie, Agatha (HarperCollins London, 2003)
So far it had been a typical New Year's Eve house party. But Mr Satterthwaite, a keen observer of human nature, sensed that the real drama of the evening was yet to unfold. And so it proved when a mysterious stranger arrived after midnight